Lactonas sesquiterpénicas de las plantas Viguiera sylvatica y Decachaeta thieleana (Asteraceae) modulan la producción de óxido nítrico y la fagocitosis de macrófagos RAW - Dupuy, Omar A. (2008)
Different species of the Asteraceae family are a potential source of sesquiterpene lactones with anti-inflammatory properties. Macrophages play a central role in the regulation of immune responses. In the present study, the in vitro effect of two sesquiterpene lactones, a millerenolide and a thieleanin, was assessed by measuring the production of nitric oxide (NO) by cell line RAW (murine macrophages) using the Griess reagent. Additionally, the effect of these sesquiterpene lactones on phagocytic capacity of latex particles and the reduction of nitroblue tetrazolium (NBT) were evaluated microscopically. Treatment of macrophages with >2.5 μg/ml of both sesquiterpene lactones, reduced the production of NO. A decreased number of macrophages able to reduce NBT were observed when these cells were treated with 3 μg/ml of millerenolide or 7.5 μg/ml of thieleanin. Treatment of macrophages with 4 μg/ml of millerenolide or 7.5 μg/ml of thieleanin, reduced the phagocytic capacity of macrophages. Cytotoxic effects on the macrophages were only observed when the concentration was increased to 8 μg/ml of millereno-lide or 25 μg/ml of thieleanin. Our results suggest that these sesquiterpene lactones could be useful compounds in the elaboration of anti-inflammatory drugs.